UTILISATION OF VIDEO CALLS TO IMPROVE ADHERENCE IN TUBERCULOSIS PATIENTS: PILOT STUDY - Nugraha, Dhanang Prawira; Rodiyah, Enik; Monica, Eva (Indonesian Journal of Pharmaceutical and Clinical Research, 2025)
Tuberculosis is the 9th leading cause of death in the world, but it takes at least 6 months to be treated. One of the challenges in tuberculosis treatment is that the treatment time is quite long, and the drugs used are also quite a lot so that it affects patient adherence in taking medication. The objective of this study was to see the effectiveness of video calls in enhancing the adherence of tuberculosis patients. The research method used was experimental pre-post noncontrol design. This study involved 12 tuberculosis patients from the Kepulungan Community Health Centre who were enrolled in the Pulmonary Tuberculosis Control Programme (Program Penanggulangan Tuberkulosis Paru/P2TB) and who met the study's inclusion and exclusion criteria. In the study, video call treatment was the independent variable while adherence was the dependent variable. The sample collection used total sampling and statistical analysis using Wilcoxon test. The findings of this investigation suggest that there is a substantial discrepancy in compliance levels between the pre- and post-video call treatment phases, as evidenced by the augmentation in the mean TB-MAS score from 102.5 to 113.6, accompanied by a p-value of 0.018 (<0.05). This shows that video calls are useful in improving patient adherence in taking antituberculosis drugs.